2015
DOI: 10.1007/s40265-015-0487-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacologic Targeting of Regulatory T Cells for Solid Organ Transplantation: Current and Future Prospects

Abstract: The last three decades have witnessed significant advances in the development of immunosuppressive medications used in kidney transplantation leading to a remarkable gain in short-term graft function and outcomes. Despite these major breakthroughs, improvements in long-term outcomes lag behind due to a stalemate between drug-related nephrotoxicity and chronic rejection typically due to donor-specific antibodies. Regulatory T cells (Tregs) have been shown to modulate the alloimmune response and can exert suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…CD4 + CD25 + Foxp3 + Treg cells play a critical role in graft tolerance induction 22 23 24 . C3 deficiency could promote CD4 + CD25 + Treg cell differentiation in STZ-induced diabetic mice 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4 + CD25 + Foxp3 + Treg cells play a critical role in graft tolerance induction 22 23 24 . C3 deficiency could promote CD4 + CD25 + Treg cell differentiation in STZ-induced diabetic mice 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have revealed that C3 deficiency is associated with attenuated Th1/Th17 responses 14 20 21 . CD4 + CD25 + Foxp3 + regulatory T (Treg) cells are thought to be critical for promoting peripheral tolerance, limiting chronic inflammatory disease and relieving autoimmune disease 22 23 24 . Strikingly, the absence of C3aR and C5aR signalling in CD4 + T cells has recently been confirmed to favour Treg expansion and survival 25 26 .…”
mentioning
confidence: 99%
“…The immunosuppressors have markedly different effects on Tregs. Calcineurin inhibitors block the expansion/function of Tregs, while mTor agents such as everolimus do not, favoring expansion and functional preservation of these cells [25]. The effect of mycophenolate on Tregs is less clear, but recent data show that at therapeutic concentrations, it potently blocks allospecific Treg function/expansion [26].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available immunosuppressive agents impact regulatory T cells in the alloimmune milieu with some of these interactions being deleterious to the allograft while others may be beneficial. 31 Variable effects are seen with common antibody induction agents such that basiliximab, an IL-2 receptor blocker, which decreases regulatory T cells, while lymphocyte-depleting agents such as antithymocyte globulin increases regulatory T cells. Calcineurin inhibitors, a mainstay of maintenance immunosuppression since the mid-1980s, seem to suppress regulatory T cells while mammalian targets of rapamycin (less commonly used in maintenance regimens) expand them.…”
Section: Tolerogenic Dendritic Cellsmentioning
confidence: 99%
“…The mechanisms of regulatory T cell suppression still remain elusive. In vitro studies have demonstrated that the immunosuppressive qualities native to regulatory T cells manifest through a variety of mechanisms, namely, modulation of antigen-presenting cell maturation and function, 32 anti-inflammatory cytokine production, 33 induction of apoptosis in target cells, 30,31 up-regulation of granzyme-B expression, 34 and disruption of metabolic pathways. 35 The general consensus throughout these studies concluded that donor antigen-specific regulatory T cells are more effective compared with polyclonal regulatory T cells.…”
Section: Tolerogenic Dendritic Cellsmentioning
confidence: 99%